2013
DOI: 10.1074/jbc.m113.493569
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide Adenine Dinucleotide-induced Multimerization of the Co-repressor CtBP1 Relies on a Switching Tryptophan

Abstract: Background: C-terminal binding protein 1 (CtBP1) assembles into a tetrameric transcriptional co-repressor but how it directs gene expression is not clear. Results: CtBP1 requires NAD(H) for transition into multimers. Its biochemical activities are separable from transcriptional repression. Conclusion: Tryptophan 318 permits CtBP1 to first dimerize and then tetramerize after the binding of NAD(H). Significance: Clarification of how CtBP1 tetramerizes will permit development of CtBP inhibitors to target oncogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(71 citation statements)
references
References 36 publications
6
59
4
Order By: Relevance
“…This is contrary to a previous report demonstrating that CtBP2 mutants lacking dehydogenase activity display corresponding decreases in corepressor activity (20). These opposing observations could be reconciled by findings in a recent study suggesting that some catalytic mutants of CtBP also display reduced binding affinity for NADH, although these mutants are still capable of forming CtBP dimers (63). Furthermore, a study by Madison et al (63) recently proposed that CtBPs not only form functional dimers, but also higher-order tetramers that are also essential to CtBP function and are controlled by a tryptophan residue (Trp318) that acts as dimerization switch following binding to NADH.…”
Section: Metabolic and Redox Sensitivity Of Ctbpscontrasting
confidence: 80%
See 1 more Smart Citation
“…This is contrary to a previous report demonstrating that CtBP2 mutants lacking dehydogenase activity display corresponding decreases in corepressor activity (20). These opposing observations could be reconciled by findings in a recent study suggesting that some catalytic mutants of CtBP also display reduced binding affinity for NADH, although these mutants are still capable of forming CtBP dimers (63). Furthermore, a study by Madison et al (63) recently proposed that CtBPs not only form functional dimers, but also higher-order tetramers that are also essential to CtBP function and are controlled by a tryptophan residue (Trp318) that acts as dimerization switch following binding to NADH.…”
Section: Metabolic and Redox Sensitivity Of Ctbpscontrasting
confidence: 80%
“…Although both forms of this dinucleotide are capable of inducing CtBP dimerization, CtBPs bind NADH with up to 100-fold higher affinity than NAD+, suggesting that these proteins are in fact sensitive to the ratio of NADH to NAD+ within the nucleus (18,61,62). Nonetheless, additional reports have suggested that CtBPs bind both NAD+ and NADH with similar affinity (17,63). Therefore, further investigation is required to determine which binding paradigm is correct.…”
Section: Metabolic and Redox Sensitivity Of Ctbpsmentioning
confidence: 99%
“…Our initial experiments were carried out using the minimal dehydrogenase domain constructs that we had previously used for crystallization, CtBP1 (28 -353) and CtBP2 (37). In contrast with a previous report (30), our SEC-MALS experiments on CtBP lacking the full C terminus showed molecular weights considerably larger than dimers in the presence of sufficient NADH (Fig. 1A).…”
Section: Mals Shows That Both Ctbp1 and Ctbp2 Assemble Into Tetramerscontrasting
confidence: 58%
“…2). This Trp has recently been implicated both as a dimerization switch in CtBP1[38] and in models of the binding of the brefeldin A (BFA) moiety in the BFA-ADP ribosyl conjugate of rat CtBP1/BARS[39]. Interestingly, the MTOB S8 atom centers over the CtBP Trp318/324 indole, rather than orienting its lone pair of electrons towards the positively charged CtBP Arg97/103, suggesting a sulfur-π interaction [40,41].…”
Section: Resultsmentioning
confidence: 99%